Mifepristone Protocol Legislation— The Anti-Choice Movement’s Disingenuous Method of Attack on the Reproductive Rights of Women and How Courts Should Respond - Samuels, Laura J. (Columbia Journal of Gender and Law, 2014)
In the past decade, five states have passed laws prohibiting the off-label use of the abortion-inducing drug mifepristone. While these laws are ostensibly passed to protect women from misuse of a dangerous drug, in actuality they represent one of the latest steps in the anti-choice movement’s efforts to dismantle the abortion right iterated in Roe v. Wade and controlled by Planned Parenthood of Southeastern Pennsylvania v. Casey. These laws prevent doctors from practicing evidence-based medicine in the manner that they believe best serves their patients, and cost women time and money while potentially exposing them to unnecessary side effects and risks. In addition, these laws force women with pregnancies of forty-nine to sixty-three days of gestation to undergo surgical abortions when medical abortions would be equally appropriate. As with most anti-choice initiatives, the women who are the most affected are those who are most vulnerable. Women without economic or family resources, those in abusive relationships, and teenagers, who often discover their pregnancies later than adult women, are required to undergo unnecessary surgical procedures and spend money and time that they cannot afford because of politically-motivated legislation without a legitimate medical rationale.